2012
DOI: 10.5812/numonthly.1623
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of loupe-Assisted Sub-inguinal Varicocelectomy in Infertile Men

Abstract: BackgroundSub-inguinal varicocelectomy is widely used among surgeons.ObjectivesThe aim of this study was to evaluate the outcome of varicocelectomy using a modified microsurgical method, specifically a loupe-assisted method, and its effects on sperm parameters in infertile men.Patients and MethodsThis study was performed in 40 patients who presented with varicocele. All patients had at least a 1-year history of infertility with abnormal semen parameters and varicocele proven by physical examination and confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 42 publications
0
5
0
1
Order By: Relevance
“…Hsieh et al [15] reported that patients with subfertile varicocelectomy had a significant improvement in sperm motility and concentration and suggested that this technique can be used as a simple, easy to apply and effective method in clinics where a surgical microscope is not available. Again, Abdelrahman et al [16] reported that they achieved more significant improvement in the concentration and motility with the loupe varicocelectomy compared to the non-microscopic varicocelectomy group. In another study, in which the results of loupe-assisted varicocelectomy were shared, the increase in motility was reported to be 46% and the mean sperm concentration was 17 X 10 6 /mL (24 -41 X 10 6 /mL) [17].…”
Section: Discussionmentioning
confidence: 98%
“…Hsieh et al [15] reported that patients with subfertile varicocelectomy had a significant improvement in sperm motility and concentration and suggested that this technique can be used as a simple, easy to apply and effective method in clinics where a surgical microscope is not available. Again, Abdelrahman et al [16] reported that they achieved more significant improvement in the concentration and motility with the loupe varicocelectomy compared to the non-microscopic varicocelectomy group. In another study, in which the results of loupe-assisted varicocelectomy were shared, the increase in motility was reported to be 46% and the mean sperm concentration was 17 X 10 6 /mL (24 -41 X 10 6 /mL) [17].…”
Section: Discussionmentioning
confidence: 98%
“…Таким образом, оперативное лечение варико-целе повышает вероятность наступления спонтан-ной беременности, а это в свою очередь связано с тем, что выполнение варикоцелэктомии достоверно улучшает сперматогенез [4,5].…”
Section: Creative Surgery and Oncologyunclassified
“…A varicocele is an abnormal dilatation, kinking, and elongation of the pampiniform venous plexus in the scrotum within the spermatic cord (6). Although the clinical varicoceles have successfully been treated traditionally by surgical techniques and in most of them, semen abnormalities improve and pregnant own spouses, however, due to the fact that a significant proportion of them remain infertile; therefore most of them referred to varieties of non-surgical treatments, various empirical drugs, herbal medicines, ART procedures, and acupuncture (7).…”
Section: Introductionmentioning
confidence: 99%